Meritocracy and economic inequality - Arrow, Kenneth J. (Kenneth Joseph), 1921-2017; Bowles, Samuel; Durlauf, Steven N. (Princeton University Press, 2000)
A collection of 12 original papers contributed by scholars, with an introduction by the editors.